Lightweight epoxy foam composite material for unmanned aerial vehicle and preparation method thereof

CN122975922APending Publication Date: 2026-10-27SHAANXI BAOTONG COMPOSITE MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611388698.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

部分泡沫芯材(如轻木、现有的开孔泡沫层等)具有吸水特性,水分自蒙皮破损处渗入后会导致芯材性能退化、重量增加,甚至引发蒙皮与芯材的界面脱粘,影响无人机蒙皮结构的长期可靠性

Benefits of technology

1、本发明兼顾了无人机的轻量化与结构强度,在闭孔发泡结构内部嵌入由玻璃纤维T型长条搭建的三维骨架。闭孔发泡结构本身密度极低,是实现轻量化的基础;而玻璃纤维骨架在X-Y平面方向上以T型长条连续排布、相邻T型长条的腹板与翼缘相互抵接,形成了连续的三维玻纤网络。该网络在X-Y平面方向(即蒙皮延展方向)上提供了连续的纤维增强路径,有效承担面内拉伸、压缩和剪切载荷;同时,T型长条的腹板在厚度方向(Z方向)上贯穿发泡结构,为三明治结构提供了直接的Z向支撑。因此,本发明以极低的泡沫密度实现了远超纯泡沫芯材的承载能力,在显著减轻结构重量的同时保证了足够的结构强度和刚度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122975922A_ABST
    Figure CN122975922A_ABST
Patent Text Reader

Abstract

The application discloses a lightweight epoxy foaming composite material for a UAV and a preparation method thereof, and belongs to the technical field of UAV materials. The preparation method comprises the following steps: preparing a T-shaped long strip by using glass fibers; building a glass fiber framework, arranging a plurality of T-shaped long strips in the same length direction and adjacent in the width direction, and making the webs of the adjacent T-shaped long strips face opposite directions and abut against the flanges of the adjacent T-shaped long strips; preparing a closed-cell foaming structure outside the glass fiber framework, and embedding the glass fiber framework into the foaming structure; and pouring epoxy resin into the gap between the glass fiber framework and the foaming structure by using a vacuum pouring method, and curing and forming. The glass fiber framework formed by the mutual abutment of the T-shaped long strips is embedded in the closed-cell foaming structure, continuous reinforcing paths are formed in the X-Y plane and the Z direction, the lightweight and structural strength are considered, the impact resistance and moisture resistance of the core material are improved, and the lightweight core material preparation is suitable for the UAV fuselage, wings and other parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of unmanned aerial vehicle (UAV) materials technology, and more specifically, to a lightweight epoxy foam composite material for UAVs and its preparation method. Background Technology

[0002] With their advantages of zero fatalities, operational flexibility, versatility, and strong environmental adaptability, unmanned aerial vehicles (UAVs) are increasingly widely used in various sectors of society. Whether for military reconnaissance, logistics delivery, or agricultural monitoring, the performance of a UAV is closely related to its weight. Lightweight design can simultaneously improve several key indicators—extending battery life, increasing payload capacity, and optimizing overall flight performance. Therefore, minimizing structural weight while ensuring structural strength is the core challenge facing UAV structural design.

[0003] In UAV structural design, a core material is typically filled between high-performance inner and outer skins. While ensuring structural load-bearing capacity using the skin, lightweighting the core material is a crucial way to reduce the overall weight of the UAV structure. Currently, commonly used core materials include polymethacrylamide (PMI) foam, polyurethane (PU) foam, polyisocyanurate (PIR) foam, and polypropylene (EPP) foam. These foam materials each have their own characteristics: PMI foam has excellent specific strength and heat resistance, making it suitable for high-performance applications; polyurethane and polyisocyanurate foams offer good thermal insulation and process adaptability; and EPP foam is renowned for its excellent impact energy absorption properties. However, existing foam sandwich materials still have the following limitations: Insufficient mechanical properties. Foam materials themselves have low strength and limited compressive and shear resistance. When used as a core layer, they mainly serve to support the skin and transfer loads, with the overall stiffness and strength of the structure relying excessively on the two side skins. Under large bending or shear loads, pure foam core materials are prone to compressive deformation or shear failure, limiting their application in load-bearing structures.

[0004] Secondly, existing foam core materials have limited reinforcement methods in the thickness direction (Z direction). Sandwich structures composed of inner and outer skins and core materials are usually only achieved through skins in the planar direction (XY direction), lacking effective fiber connections or reinforcement structures in the thickness direction. This results in sandwich structures being weak under loads perpendicular to the panel direction, with insufficient interlaminar shear strength and peel resistance, and prone to debonding at the interface between the skin and the core material.

[0005] Some existing foam core materials lack sufficient impact resistance. During drone takeoff and landing, transportation, or accidental collisions, the core layer is susceptible to impact loads. Open-cell foams or low-density foams are prone to irreversible compressive deformation after impact, leading to a decline in structural performance.

[0006] Existing foam core materials have insufficient moisture-proof performance. Some foam core materials (such as balsa wood and existing open-cell foam layers) have water-absorbing properties. When moisture seeps in through the damaged areas of the skin, it can lead to performance degradation of the core material, increased weight, and even debonding of the skin and core material interface, affecting the long-term reliability of the UAV skin structure.

[0007] In view of the above, the present invention is proposed to solve the aforementioned technical problems. Summary of the Invention The purpose of this invention is to provide a lightweight epoxy foam composite material for unmanned aerial vehicles and its preparation method, so as to solve the above-mentioned technical problems.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a lightweight epoxy foam composite material for unmanned aerial vehicles (UAVs) includes the following steps: T-shaped strips were prepared using glass fiber. A fiberglass skeleton is constructed and configured as follows: several T-shaped strips are distributed adjacently along the width direction with the same length direction. The web of the T-shaped strips divides one side of the flange into two receiving areas. The webs of two adjacent T-shaped strips face opposite directions. The web of the T-shaped strip is located in the receiving area of ​​the adjacent T-shaped strip facing that web and abuts against the flange of the adjacent T-shaped strip. A closed-cell foam structure is prepared outside the obtained glass fiber skeleton, thereby embedding the glass fiber skeleton into the foam structure; The epoxy resin is vacuum-injected into the gap between the glass fiber skeleton and the foam structure using a vacuum-assisted resin transfer molding method. The epoxy resin is then cured to obtain a lightweight epoxy foam composite material for UAVs.

[0009] Optionally, the vacuum-assisted resin transfer molding method includes the following steps: In the fiberglass skeleton, foam structures are inserted through both ends of the T-shaped strips. The foam structures are placed in a vacuum-sealed bag, which seals and isolates the two cavities at the middle of the foam structure along the length of the T-shaped strips. A vacuum pump is used to evacuate the foam structures, removing the air from the gaps between the fiberglass skeleton and the foam structures, creating a negative pressure environment at the gaps. Liquid epoxy resin is injected from one side of the fiberglass skeleton along the length of the T-shaped strips. After the resin completely impregnates and fills the gaps, it is left to stand at room temperature or heated to allow the epoxy resin to cure and solidify.

[0010] Alternatively, a closed-cell foam structure can be prepared on the outside of the obtained glass fiber skeleton using polyisocyanurate material.

[0011] Alternatively, a closed-cell foam structure can be prepared on the outside of the obtained glass fiber skeleton using polyurethane material.

[0012] Optionally, the foam density of the foamed structure is 10-30 kg / m³.3 .

[0013] Optionally, E-glass fiber with no twist roving is used, which is arranged, impregnated with epoxy resin, pre-formed into a continuous T-shaped strip structure, and then cut into T-shaped strips after thermoforming and curing.

[0014] Optionally, the epoxy resin comprises, by parts by weight: 40-100 parts of bisphenol A type epoxy resin matrix; 10-20 parts toughening agent; 5-25 parts of thermally conductive filler with a thickness of 0-30μm; 20-50 parts of curing agent.

[0015] Optionally, by weight, the epoxy resin further includes: 0.5-4 parts coupling agent; 0-1 part defoamer.

[0016] According to another aspect of the present invention, a lightweight epoxy foam composite material for unmanned aerial vehicles is provided, which is prepared by the aforementioned preparation method.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention balances lightweight design with structural strength in drones by embedding a three-dimensional skeleton constructed from T-shaped glass fiber strips within a closed-cell foam structure. The extremely low density of the closed-cell foam structure is fundamental to its lightweight design; the glass fiber skeleton, arranged continuously in T-shaped strips in the XY plane, with the webs of adjacent T-shaped strips abutting against the flanges, forms a continuous three-dimensional glass fiber network. This network provides continuous fiber reinforcement paths in the XY plane (i.e., the skin extension direction), effectively bearing in-plane tensile, compressive, and shear loads. Simultaneously, the webs of the T-shaped strips penetrate the foam structure in the thickness direction (Z direction), providing direct Z-axis support for the sandwich structure. Therefore, this invention achieves a load-bearing capacity far exceeding that of pure foam core materials with extremely low foam density, significantly reducing structural weight while ensuring sufficient structural strength and stiffness.

[0018] This invention employs a process route of first preparing a closed-cell foam structure on the outside of a glass fiber skeleton, and then vacuum-infusing epoxy resin. Because the foam structure is a closed-cell system, its pores do not absorb resin; the resin only fills the gaps between the glass fiber skeleton and the foam structure. Therefore, the amount of resin used is controllable, preventing excessive resin absorption by the foam structure from increasing the weight of the core material. Simultaneously, after the epoxy resin in the gaps cures, a strong mechanical and chemical bonding interface is formed between the glass fiber surface and the inner wall of the foam structure. The glass fiber skeleton, epoxy resin, and foam structure are tightly bonded into a single unit, effectively improving the interfacial bonding strength between the materials within the core material and reducing the risk of delamination due to interfacial debonding.

[0019] 2. This invention improves the impact and damage resistance of the core material layer. The closed-cell foam structure in this invention, with its independently sealed cells, allows for instantaneous compression of the gas inside the cells under impact loads, increasing gas pressure and converting impact kinetic energy into internal gas energy, thus achieving energy absorption. Simultaneously, the elastic deformation of the cell walls also dissipates some impact energy. This energy absorption mechanism is independent of whether the cells are open or closed; closed-cell foam also possesses energy absorption capabilities. More importantly, the three-dimensional glass fiber skeleton embedded within the foam structure provides support for the foam, effectively limiting large local deformations under impact loads and preventing collapse of the impact area. Therefore, this invention maintains the excellent moisture-proof performance of closed-cell foam while possessing good impact resistance and energy absorption characteristics.

[0020] 3. This invention improves the moisture resistance and weather resistance of drones. The invention uses a closed-cell foam structure as the matrix. Each bubble in the closed-cell foam is an independent, sealed micro-chamber, not interconnected. Even if the drone skin is damaged, moisture is difficult to penetrate and diffuse within the foam structure, limiting moisture intrusion to the vicinity of the damaged area and preventing large-scale water absorption, weight gain, and performance degradation in the core material. Simultaneously, the closed-cell structure also prevents moisture accumulation at the interface between the skin and the core material, effectively reducing the risk of interface debonding and ensuring the long-term reliability of the drone skin structure in humid environments.

[0021] 4. This invention improves the stability of the bonding state between the core material and the skin. Existing core material layers have poor mechanical properties, relying entirely on the skin to bear bending or shear loads. Pure foam core materials are prone to compressive deformation or shear failure, which can easily lead to excessive deformation of the skin and damage to the core material layer, resulting in debonding between the skin and the core material. This invention improves the impact and damage resistance of the core material layer, enabling it to share loads with the skin and reducing its own risk of breakage and deformation, thus improving the interfacial bonding state between the core material layer and the skin.

[0022] 5. This invention, while ensuring the aforementioned mechanical properties, improves the surface adaptability and structural design flexibility of the core material layer. In this invention, the three-dimensional glass fiber skeleton is constructed from several T-shaped strips. The webs of adjacent T-shaped strips face opposite directions, and the webs of each T-shaped strip are located within the receiving area of ​​the adjacent T-shaped strip and abut against its flange. This abutment relationship is an adjustable angular fit, rather than a rigid snap-fit ​​or fixed connection that cannot be deformed. During the manufacturing process, the abutment angle between adjacent T-shaped strips can be adjusted according to the three-dimensional shape of the UAV skin to make the overall shape of the glass fiber skeleton adapt to the curved skin. At the same time, the dimensions of the T-shaped strips (such as web height, flange width, etc.) can be adjusted according to the actual needs of different parts, flexibly adapting to different structural spaces such as wide and narrow slots. This design enables this invention to adapt to structural parts with different curvatures and thicknesses, such as the UAV fuselage and wings, and has good structural design flexibility. Attached Figure Description

[0023] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments and descriptions of the invention are used to explain the invention, but do not constitute an undue limitation of the invention. Obviously, the drawings described below are merely some embodiments, and those skilled in the art can obtain other drawings based on these drawings without creative effort. In the drawings: Figure 1 This is a schematic diagram of the structure of a glass fiber skeleton provided in an embodiment of this application.

[0024] Figure 2 This is a schematic diagram of the structure of a glass fiber skeleton provided in an embodiment of this application.

[0025] Attached image label: 100, T-shaped strip. Detailed Implementation

[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0027] This invention provides a lightweight epoxy foam composite material for unmanned aerial vehicles (UAVs) and its preparation method, which includes the following steps: T-shaped strips 100 were prepared using glass fiber; A fiberglass skeleton is constructed and configured as follows: several T-shaped strips 100 are distributed adjacently along the width direction with the same length direction. The web of the T-shaped strip 100 divides one side of the flange into two receiving areas. The webs of two adjacent T-shaped strips 100 face opposite directions. The web of the T-shaped strip 100 is located in the receiving area of ​​the adjacent T-shaped strip 100 facing the web and abuts against the flange of the adjacent T-shaped strip 100. A closed-cell foam structure is prepared outside the obtained glass fiber skeleton, thereby embedding the glass fiber skeleton into the foam structure; The epoxy resin is vacuum-injected into the gap between the glass fiber skeleton and the foam structure using a vacuum-assisted resin transfer molding method. The epoxy resin is then cured to obtain a lightweight epoxy foam composite material for UAVs.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention balances lightweight design with structural strength in unmanned aerial vehicles (UAVs) by embedding a three-dimensional skeleton constructed from glass fiber T-shaped strips 100 within a closed-cell foam structure. The closed-cell foam structure itself has extremely low density, which is fundamental to achieving lightweight design. The glass fiber skeleton is formed by continuous T-shaped strips 100 arranged in the XY plane, with the webs of adjacent T-shaped strips 100 abutting against the flanges, creating a continuous three-dimensional glass fiber network. This network provides continuous fiber reinforcement paths in the XY plane (i.e., the skin extension direction), effectively bearing in-plane tensile, compressive, and shear loads. Simultaneously, the webs of the T-shaped strips 100 penetrate the foam structure in the thickness direction (Z direction), providing direct Z-axis support for the sandwich structure. Therefore, this invention achieves a load-bearing capacity far exceeding that of pure foam core materials with extremely low foam density, significantly reducing structural weight while ensuring sufficient structural strength and stiffness.

[0029] This invention employs a process route of first preparing a closed-cell foam structure on the outside of a glass fiber skeleton, and then vacuum-infusing epoxy resin. Because the foam structure is a closed-cell system, its pores do not absorb resin; the resin only fills the gaps between the glass fiber skeleton and the foam structure. Therefore, the amount of resin used is controllable, preventing excessive resin absorption by the foam structure from increasing the weight of the core material. Simultaneously, after the epoxy resin in the gaps cures, a strong mechanical and chemical bonding interface is formed between the glass fiber surface and the inner wall of the foam structure. The glass fiber skeleton, epoxy resin, and foam structure are tightly bonded into a single unit, effectively improving the interfacial bonding strength between the materials within the core material and reducing the risk of delamination due to interfacial debonding.

[0030] 2. This invention improves the impact and damage resistance of the core material layer. The closed-cell foam structure in this invention, with its independently sealed cells, allows for instantaneous compression of the gas inside the cells under impact loads, increasing gas pressure and converting impact kinetic energy into internal gas energy, thus achieving energy absorption. Simultaneously, the elastic deformation of the cell walls also dissipates some impact energy. This energy absorption mechanism is independent of whether the cells are open or closed; closed-cell foam also possesses energy absorption capabilities. More importantly, the three-dimensional glass fiber skeleton embedded within the foam structure provides support for the foam, effectively limiting large local deformations under impact loads and preventing collapse of the impact area. Therefore, this invention maintains the excellent moisture-proof performance of closed-cell foam while possessing good impact resistance and energy absorption characteristics.

[0031] 3. This invention improves the moisture resistance and weather resistance of drones. The invention uses a closed-cell foam structure as the matrix. Each bubble in the closed-cell foam is an independent, sealed micro-chamber, not interconnected. Even if the drone skin is damaged, moisture is difficult to penetrate and diffuse within the foam structure, limiting moisture intrusion to the vicinity of the damaged area and preventing large-scale water absorption, weight gain, and performance degradation in the core material. Simultaneously, the closed-cell structure also prevents moisture accumulation at the interface between the skin and the core material, effectively reducing the risk of interface debonding and ensuring the long-term reliability of the drone skin structure in humid environments.

[0032] 4. This invention improves the stability of the bonding state between the core material and the skin. Existing core material layers have poor mechanical properties, relying entirely on the skin to bear bending or shear loads. Pure foam core materials are prone to compressive deformation or shear failure, which can easily lead to excessive deformation of the skin and damage to the core material layer, resulting in debonding between the skin and the core material. This invention improves the impact and damage resistance of the core material layer, enabling it to share loads with the skin and reducing its own risk of breakage and deformation, thus improving the interfacial bonding state between the core material layer and the skin.

[0033] 5. While ensuring the aforementioned mechanical properties, this invention improves the surface adaptability and structural design flexibility of the core material layer. In this invention, the three-dimensional glass fiber skeleton is constructed from several T-shaped strips 100. The webs of adjacent T-shaped strips 100 face opposite directions, and the webs of each T-shaped strip 100 are located within the receiving area of ​​the adjacent T-shaped strip 100 and abut against its flange. This abutment relationship is an adjustable angular fit, rather than a rigid snap-fit ​​or fixed connection that cannot be deformed. During the manufacturing process, the abutment angle between adjacent T-shaped strips 100 can be adjusted according to the three-dimensional shape of the UAV skin to make the overall shape of the glass fiber skeleton adapt to the curved skin. At the same time, the dimensions of the T-shaped strips 100 (such as web height, flange width, etc.) can be adjusted according to the actual needs of different parts, flexibly adapting to different structural spaces such as wide and narrow slots. This design enables this invention to adapt to structural parts with different curvatures and thicknesses, such as the UAV fuselage and wings, and has good structural design flexibility.

[0034] In one possible implementation, the vacuum-assisted resin transfer molding method includes the following steps: In the fiberglass skeleton, foam structures are inserted through both ends of the body length of all T-shaped strips 100. The foam structures are placed in a vacuum sealing bag, which seals and isolates the two side cavities at the middle of the foam structure along the body length of the T-shaped strips 100. The air between the fiberglass skeleton and the foam structure is removed by using a vacuum pump, creating a negative pressure environment at the gaps. Liquid epoxy resin is injected from one side of the fiberglass skeleton along the body length of the T-shaped strips 100. After the resin completely impregnates and fills the gaps, the mixture is left to stand at room temperature or heated to cure and form the epoxy resin.

[0035] This invention involves suction and injection from one side of the fiberglass skeleton. Since the length direction of the fiberglass skeleton is consistent with the extension direction of the T-shaped strip 100, this side is the open end of the skeleton. Vacuuming from this side can establish a connected negative pressure channel in the entire gap network. Under the drive of negative pressure, liquid epoxy resin is sucked in from the same side and gradually advanced along the gap network, which can fully wet all gap areas between the fiberglass skeleton and the foam structure, including complex geometric parts such as the intersection of the web and flange of the T-shaped strip 100. This effectively avoids injection defects such as bubbles and dry spots, and ensures the integrity and uniformity of resin filling. Meanwhile, because the independent closed pores of the closed-cell foam structure in this invention do not draw in resin under vacuum negative pressure, the resin only fills the gaps between the fiberglass skeleton and the foam structure. Injection is done through one side of the body, and the resin overflows after completely filling the gaps, marking the injection endpoint. Operators can visually determine when filling is complete; when resin overflows from the outlet, it indicates the gaps are completely filled, at which point injection can be stopped for precise resin control. This method of determining the endpoint by the complete filling of the gaps avoids unnecessary weight gain due to over-injection of resin, ensuring the lightweight effect of the core material. After the epoxy resin is injected, it is cured by either room temperature standing or heating. Room temperature standing curing is simple and requires no additional equipment, while heating curing accelerates the curing reaction and shortens the molding cycle. The choice between the two methods can be flexibly adjusted according to actual production conditions and efficiency requirements. The cured epoxy resin bonds the fiberglass skeleton and the foam structure into a whole, ensuring interfacial bonding strength, and ultimately resulting in stable and reliable mechanical properties of the core material.

[0036] Furthermore, the process arrangement of suction from one side of the fiberglass skeleton and injection from the same side allows for vacuuming and resin injection operations to be performed on the same side, simplifying mold design and operational procedures. The more centralized arrangement of the vacuum pump and resin injection equipment reduces the difficulty of pipeline connections and sealing, improving operational convenience and production efficiency, making it suitable for mass production of UAV core materials. Finally, the infusion process works in conjunction with the closed-cell foam structure. The closed-cell foam structure does not draw in resin under vacuum negative pressure, so the resin is not consumed additionally due to foam adsorption during the infusion process. This means that the final weight gain of the core material mainly comes from the epoxy resin filling the gaps, making the overall weight controllable and predictable, further ensuring the lightweight goal of the core material.

[0037] In one possible implementation, a closed-cell foam structure is prepared on the outside of the obtained glass fiber skeleton using polyisocyanurate or polyurethane materials.

[0038] Polyisocyanurate foam possesses a high closed-cell ratio, low foam density, and high strength. While achieving lightweight design, it provides effective lateral support to the fiberglass skeleton, constraining buckling deformation under compression. The closed-cell structure effectively prevents epoxy resin intrusion during vacuum infusion, ensuring the resin only fills the gaps between the fiberglass skeleton and the foam structure. This allows for precise control of the core material's final weight, avoiding unnecessary weight gain due to excessive resin absorption. Furthermore, polyisocyanurate material exhibits strong wide-temperature tolerance and some flame-retardant properties, beneficial for temperature management and flight safety in UAV equipment compartments. Its good dimensional stability and low shrinkage rate make the core layer dimensions more stable and controllable.

[0039] The reaction rate of polyurethane foam systems can be widely adjusted by the type and amount of catalyst. This allows for rapid curing to meet the demands of high-efficiency production, while also extending the workable time to accommodate the filling requirements of complex mold shapes. This is crucial for completely encapsulating the fiberglass skeleton and forming a uniform foam structure, demonstrating strong adaptability to molding processes. Simultaneously, the low initial viscosity and good flowability of the polyurethane resin system allow it to fully impregnate and penetrate all parts of the fiberglass skeleton before the foaming reaction occurs. This ensures a tight encapsulation between the fiberglass and the foam without significant macroscopic defects, thereby guaranteeing the integrity of the core layer.

[0040] Furthermore, the mechanical properties of polyurethane foam can be designed within a wide range. By adjusting the types and ratios of polyols and isocyanates, performance can be adjusted from soft to rigid, allowing for customized development based on the stiffness requirements of different drone components. Polyurethane foam possesses naturally excellent adhesion to various substrates. During vacuum infusion of epoxy resin, it forms a good interfacial bond with the epoxy resin impregnated in the gaps, avoiding delamination problems caused by insufficient interfacial compatibility of dissimilar materials. The inherent toughness of polyurethane material allows it to absorb and dissipate impact energy to a certain extent. Combined with the restraining effect of the fiberglass skeleton on foam deformation, this further enhances the core layer's resistance to impact deformation, contributing to the structural safety of drones during takeoff, landing, and transportation.

[0041] In one possible implementation, the foam density of the foamed structure is 10-30 kg / m³. 3 This application controls the foam density at a low level, which firstly directly reduces the weight of the core layer, contributing to the structural weight reduction for improved drone endurance; secondly, low-density foam is more prone to compression deformation under impact loads, enabling it to absorb and dissipate impact energy more efficiently; simultaneously, lower density means less foaming material is used, helping to reduce material costs; furthermore, low-density closed-cell foam has weaker capillary adsorption of resin during vacuum infusion, and combined with the physical barrier of the closed-cell structure against resin intrusion, it can prevent additional resin from seeping into the cells and causing weight gain, making the final core weight more controllable.

[0042] In one possible implementation, E-glass fiber with no twist is used, the yarn is laid out, impregnated with epoxy resin, pre-formed into a continuous T-shaped strip 100 structure, and then cut into T-shaped strips 100 after thermoforming and curing.

[0043] In one possible implementation, the epoxy resin comprises, by weight parts: 40-100 parts of bisphenol A type epoxy resin matrix; 10-20 parts of toughening agent, such as carboxyl-terminated butadiene-acrylonitrile rubber, hydroxyl-terminated butadiene-acrylonitrile rubber, liquid polysulfide rubber, polyurethane prepolymer, and polyetheramines, or nano-sized particle toughening agents such as nano-silica and nano-calcium carbonate, are used. When a drone encounters airflow or accidental collisions during takeoff, landing, or flight, its structure is subjected to impact. The toughening agent can improve the resin's toughness while maintaining its strength: it forms a special microstructure in the resin matrix. When impacted, these structures can absorb and disperse impact energy through shear yielding, cavitation effects, etc., preventing crack propagation, thereby significantly improving the material's impact strength and ensuring the reliability of the drone structure under complex loads. 5-25 parts of thermally conductive fillers with a particle size of 0-30μm, such as alumina fillers, aluminum nitride fillers, boron nitride fillers, silicon carbide fillers, or a mixture of various fillers, can also be used in different particle sizes, as long as the total mass of the fillers meets the relevant proportion requirements. For example, 4-15 parts of large particle size (such as 35-50μm alumina), 1-6 parts of medium particle size (such as 5-7μm or 10-12μm aluminum nitride), and 0.5-4 parts of small particle size (such as 1-4μm silicon carbide). During the flight and take-off and landing of UAVs, vibration and impact will cause elastic deformation of the fiberglass skeleton and micro-friction at the foam interface. Both of these will generate local heat inside the fiberglass skeleton and at the interface with the foam. To reduce the risk of decreased mechanical properties of epoxy resin sealant due to localized temperature rise, thereby reducing its adhesion and constraint capabilities to glass fiber; and considering the difference in thermal expansion coefficients between glass fiber and foam, to reduce the risk of microcracks initiating at the interface and inducing interface debonding, this invention adds thermally conductive fillers to the epoxy resin. This allows locally generated heat to be rapidly conducted along the gaps to the foamed structure with a larger heat capacity, enabling the heat to be evenly distributed over a wider area. This reduces the temperature rise and thermal stress concentration at the interface, thereby protecting the integrity of the interface bond, delaying the thermo-oxidative aging of the resin, and improving the fatigue life and structural reliability of the core layer under continuous vibration. 20-50 parts of curing agent; 0.5-4 parts of coupling agent act as a bridging agent. One end of the molecule can react chemically with the silanol groups on the surface of glass fiber to form a chemical bond, while the other end cross-links or entangles with the epoxy resin molecular chain, thereby establishing a strong interfacial bond between the glass fiber skeleton and the epoxy resin, effectively improving the interfacial compatibility between the fiber and the resin, enhancing stress transfer efficiency, and reducing performance degradation caused by interfacial debonding. 0-1 part of defoamer: The presence of trace amounts of defoamer during vacuum infusion can reduce the surface tension of liquid resin, promote the discharge and rupture of internal bubbles, and further reduce the porosity defects inside the cured epoxy resin in conjunction with the vacuum negative pressure environment, ensuring the density and mechanical integrity of the resin filler.

[0044] To better illustrate the present invention, the following embodiments are provided: Preparation of T-shaped strip 100: T-shaped strips of 100mm were prepared using a pultrusion process. The reinforcing material was E-glass fiber untwisted roving with a linear density of 2400 Tex, supplemented with E-glass fiber continuous mat (area density 300 g / m²) to provide transverse reinforcement. The fibers were unwound from the yarn rack, bundled by a guide plate, and then impregnated in a resin bath. The epoxy resin used for impregnation was bisphenol A type epoxy resin E-51, the curing agent was methyltetrahydrophthalic anhydride, and the accelerator was benzyl dimethylamine. After passing through the resin bath, the fibers entered a pre-forming mold with a compression ratio set at 2.0:1, gradually compressing to the T-shaped cross-section. They then entered a three-stage heated mold, 900mm in length, with the three temperatures set as follows: preheating zone 160℃, gel zone 180℃, and curing zone 200℃. The traction speed was set at 400mm / min. The profile is fully cured at the mold exit and pulled out by a tracked traction device (traction force 150kN). It is then cut into T-shaped strips 100mm in length by a fixed-length cutting saw. The cross-sectional dimensions of the T-shaped strip 100 are: flange width 20mm, flange thickness 3mm, web height 15mm, and web thickness 3mm.

[0045] Construct a fiberglass framework using 100mm T-shaped strips: Take several T-shaped strips of length 100mm as described above, and arrange them adjacently along the width direction, maintaining a consistent length (100mm direction). For example... Figure 2 The T-shaped strips 100 are arranged such that the webs of adjacent T-shaped strips 100 face opposite directions, so that the webs of each T-shaped strip 100 are located within the receiving area of ​​the adjacent T-shaped strip 100 facing its web. The ends of the webs abut against the inner side of the flanges of the adjacent T-shaped strips 100. This arrangement forms a fiberglass skeleton composed of the T-shaped strips 100 abutting against each other. The planar dimensions of the skeleton are 300mm × 200mm, and the thickness is 21mm (3mm flange thickness + 15mm web height + 3mm thickness of the other flange).

[0046] Preparation of closed-cell foam structure: A closed-cell polyisocyanurate foam structure was prepared on the outside of a glass fiber skeleton. The foaming raw materials were divided into component A and component B. Component A was the isocyanate component, using polymethylene polyphenyl isocyanate (PAPI) at a dosage of 100 parts by weight. Component B was the polyol component, comprising: 60 parts of polyester polyol (hydroxyl value approximately 350 mg KOH / g), 40 parts of polyether polyol (hydroxyl value approximately 400 mg KOH / g), 25 parts of blowing agent HCFC-141b, 3 parts of composite catalyst (a combination of tertiary amine catalyst and organotin catalyst), and 1.5 parts of foam stabilizer (polysiloxane). The molar ratio of isocyanate groups to active hydrogen in the polyol was controlled at 4:1.

[0047] Components A and B were preheated to 25°C and rapidly mixed at a mass ratio of A:B = 100:110. After stirring for 10 seconds, the mixture was immediately poured into a mold containing a fiberglass skeleton. The mixture freely foamed within the mold. After approximately 120 seconds of foaming, the foam volume stopped increasing. At this point, the mold was placed in an 80°C oven for post-curing and held at that temperature for 2 hours. After demolding, a preform with a fiberglass skeleton embedded within a polyisocyanurate closed-cell foam structure was obtained. The apparent density of the foam structure was measured to be 20 kg / m³, and the closed-cell rate was ≥92%. Excess foam structure along both sides of the T-shaped strip 100 was removed to ensure that foam structures penetrated both ends of the length of all T-shaped strips 100 within the fiberglass skeleton.

[0048] Vacuum-assisted resin infusion: The preform is placed in a vacuum injection mold (the aforementioned vacuum sealing bag). The vacuum sealing bag seals and isolates the two cavities at the middle of the foam structure along the length of the T-shaped strip 100. The vacuuming and overflow observation side of the vacuum sealing bag is on the same side of the skeleton along the length of the T-shaped strip 100 (the vacuuming pipe is transparent, allowing observation of whether resin overflows into the pipe, and a valve is provided; if overflow into the vacuuming pipe is observed, the valve of the vacuuming pipe is immediately closed to stop the vacuum pump), and the glue injection operation side is on the other side.

[0049] The formulation of epoxy resin for vacuum infusion (by parts by weight) is as follows: Bisphenol A type epoxy resin E-51: 100 parts; Toughening agent: 15 parts of carboxyl-terminated butadiene-acrylonitrile rubber (CTBN); Thermally conductive filler: spherical alumina, using a three-stage gradation—12 parts of 35-50μm particle size, 5 parts of 5-7μm particle size, and 3 parts of 1-4μm particle size, for a total of 20 parts filler; Curing agent: 85 parts of methylhexahydrophthalic anhydride (MeHHPA); Accelerator: 0.8 parts of benzyl dimethylamine (BDMA); Coupling agent: 2 parts of γ-aminopropyltriethoxysilane (KH-550); Defoamer: 0.3 parts of polydimethylsiloxane; Weigh the above components according to the specified proportions and place them in a vacuum mixer. Mix under a vacuum of -0.09 MPa for 30 minutes, then continue vacuum degassing for 15 minutes. The viscosity of the mixed resin system at 25°C is approximately 1200 mPa·s.

[0050] Place the mixed and degassed epoxy resin in an open resin tank. Seal one end of a guide tube to the operating port on the vacuum sealing bag injection side, and insert the other end below the liquid surface in the resin tank. Close the valve of the guide tube. Turn on the vacuum pump and evacuate the vacuum level in the sealed system to -0.095 MPa (approximately 5 kPa absolute pressure), removing the air from the gaps between the fiberglass skeleton and the foamed structure, creating a negative pressure environment at the gaps. Maintain the vacuum state for 30 minutes to fully remove the air from the gaps between the fiberglass skeleton and the foamed structure.

[0051] Open the valve on the inlet tube. Under atmospheric pressure (approximately 0.1 MPa), liquid epoxy resin is drawn into the sealed system through the feed pipe. The liquid epoxy resin is injected into the bag from one side along the 100mm length of the T-shaped strip from the fiberglass skeleton, flowing through the gaps between the fiberglass skeleton and the foam structure to the overflow observation side on the other side of the bag. The overflow observation side is continuously monitored during the injection process. When resin overflows from the overflow observation side, it indicates that all gaps have been completely filled. At this point, the vacuum pump is turned off, the valve on the inlet tube is closed, and the injection process is stopped. The entire injection process takes approximately 45 minutes.

[0052] After infusion, maintain a vacuum seal and place the vacuum-sealed bag in an oven to cure according to the following curing regime: 80℃ for 2 hours, 120℃ for 2 hours, and 150℃ for 4 hours. After curing, allow it to cool naturally to room temperature and demold to obtain the lightweight epoxy foam composite material for drones.

[0053] The performance of the prepared lightweight epoxy foam composite material for UAVs (hereinafter referred to as core material) was tested.

[0054] The overall density of the core material was determined to be 95 kg / m³ according to GB / T 6343. The sample size was 50 mm × 50 mm × 21 mm, and the loading speed was 2 mm / min. The compressive strength was measured to be 2.8 MPa, and the compressive modulus was 85 MPa. A three-point bending test of the sandwich structure was conducted according to GB / T 1456. The sample size was 300 mm × 50 mm × 21 mm, the span was 200 mm, and the loading speed was 5 mm / min. The flexural strength was measured to be 18.5 MPa, and the flexural modulus was 2.1 GPa. The thermal conductivity was determined to be 0.18 W / (m·K) according to GB / T 10294 (steady-state hot plate method). A foamed structure was cut from the core material, and the closed-cell rate of the foamed structure was measured to be 92%.

[0055] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a lightweight epoxy foam composite material for unmanned aerial vehicles (UAVs), characterized in that, Includes the following steps: T-shaped strips were prepared using glass fiber. A fiberglass skeleton is constructed and configured as follows: several T-shaped strips are distributed adjacently along the width direction with the same length direction. The web of the T-shaped strips divides one side of the flange into two receiving areas. The webs of two adjacent T-shaped strips face opposite directions. The web of the T-shaped strip is located in the receiving area of ​​the adjacent T-shaped strip facing that web and abuts against the flange of the adjacent T-shaped strip. A closed-cell foam structure is prepared outside the obtained glass fiber skeleton, thereby embedding the glass fiber skeleton into the foam structure; The epoxy resin is vacuum-injected into the gap between the glass fiber skeleton and the foam structure using a vacuum-assisted resin transfer molding method. The epoxy resin is then cured to obtain a lightweight epoxy foam composite material for UAVs.

2. The method for preparing lightweight epoxy foamed composite material for UAVs according to claim 1, characterized in that, The vacuum-assisted resin transfer molding method includes the following steps: In the fiberglass skeleton, foam structures are inserted through both ends of the body length of all T-shaped strips. The foam structures are placed in a vacuum-sealed bag. The vacuum-sealed bag seals and isolates the two cavities at the middle of the foam structure along the body length of the T-shaped strips. A vacuum pump is used to evacuate the foam structure, removing the air between the fiberglass skeleton and the foam structure, creating a negative pressure environment at the gaps. Liquid epoxy resin is injected from one side of the fiberglass skeleton along the body length of the T-shaped strips. After the resin completely impregnates and fills the gaps, it is left to stand at room temperature or heated to allow the epoxy resin to cure and form.

3. The method for preparing lightweight epoxy foamed composite material for UAVs according to claim 2, characterized in that, Closed-cell foam structures were prepared on the outside of the obtained glass fiber skeleton using polyisocyanurate material.

4. The method for preparing lightweight epoxy foamed composite material for UAVs according to claim 1, characterized in that, Closed-cell foam structures were prepared on the outside of the obtained glass fiber skeleton using polyurethane materials.

5. The method for preparing lightweight epoxy foamed composite material for UAVs according to claim 1, characterized in that, The foam density of the foamed structure is 10-30 kg / m³. 3 .

6. The method for preparing lightweight epoxy foamed composite material for UAVs according to claim 1, characterized in that, E-glass fiber with no twisted roving is used. The yarn is laid out, impregnated with epoxy resin, pre-formed into a continuous T-shaped long strip structure, and then cut into T-shaped long strips after thermoforming and curing.

7. The method for preparing lightweight epoxy foamed composite material for UAVs according to claim 1, characterized in that, The epoxy resin comprises, by weight parts: 40-100 parts of bisphenol A type epoxy resin matrix; 10-20 parts toughening agent; 5-25 parts of thermally conductive filler with a thickness of 0-30μm; 20-50 parts of curing agent.

8. The method for preparing lightweight epoxy foamed composite material for UAVs according to claim 7, characterized in that, By weight, the epoxy resin further includes: 0.5-4 parts coupling agent; 0-1 part defoamer.

9. A lightweight epoxy foam composite material for unmanned aerial vehicles (UAVs), characterized in that, It is prepared using the preparation method of lightweight epoxy foam composite material for UAVs as described in any one of claims 1-8.